2020
DOI: 10.37185/lns.1.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: From Ancient Spice to Modern Anti-Viral Drug in COVID-19 Pandemic

Abstract: A viral disease such as COVID-19 (Corona Virus Disease-2019) is a major health problem and worsens the complications of various diseases including cardiovascular diseases, hypertension, diabetes, and cancers. The current study summarises the therapeutic progress and efficacy of curcumin for the cure and prevention of severe acute respiratory syndrome (SARS) and SARS-related COVID-19. Curcumin is extracted from the herb Curcuma longa L., known for its various therapeutic functions such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Due to the several unique properties of curcumin and its beneficial effects on different aspects of human health, several reviews and also some clinical trials have recently suggested that curcumin might have beneficial effects on signs and symptoms of COVID-19 [ 6 , 19 , 23 27 ]. Results from clinical trials showed that curcumin as a natural polyphenolic compound could be a potential treatment for COVID-19 infection [ 19 , 23 , 25 , 28 ]. A review study reported some of the potential effects of curcumin such as inhibiting the entry of viruses to the cell, inhibiting encapsulation of the virus and viral protease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the several unique properties of curcumin and its beneficial effects on different aspects of human health, several reviews and also some clinical trials have recently suggested that curcumin might have beneficial effects on signs and symptoms of COVID-19 [ 6 , 19 , 23 27 ]. Results from clinical trials showed that curcumin as a natural polyphenolic compound could be a potential treatment for COVID-19 infection [ 19 , 23 , 25 , 28 ]. A review study reported some of the potential effects of curcumin such as inhibiting the entry of viruses to the cell, inhibiting encapsulation of the virus and viral protease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin can interact with spike proteins or angiotensin 2 (ACE2) proteins in the signalling pathway induced by COVID-19. Curcumin also inhibits several important signalling pathways in viral infection, such as transcription factors (NF-κB, signal transducer and activator of transcription 3 (STAT-3), Vnt/b-catenin, nuclear factor E2-related factor (Nrf2), p38/MAPK, and virus-induced inflammation by modulating the manifestation of various factors (IL-10, Interleukin-18 (IL-18), IL-6, tumour necrosis factor (TNF) α/β and COX-2) in COVID-19 [ 153 , 154 ]. Valizadeha et al investigated the effect of nanocurcumin on the modulation of inflammatory cytokines in patients with COVID-19.…”
Section: Biological Activities Of Curcuminmentioning
confidence: 99%
“…A study has shown that curcumin, in addition to its antioxidant effects by activating the Nrf2 pathway and induction of Glutathione (GSH) production, inactivates influenza A virus infection and alleviates the impacts of COVID-19 [7]. Many studies have also shown that sulforaphane (SFN), a natural compound derived from broccoli sprouts, suppresses viral replication in respiratory diseases such as influenza A and hepatitis C virus (HCV) and Herpes simplex virus 1 (HSV-1).…”
mentioning
confidence: 99%